Dietary Management of Children With Super-Refractory Status Epilepticus: A Systematic Review and Experience in a Single UK Tertiary Centre - Schoeler, Natasha E.; Simpson, Zoe; Zhou, Runming; Pujar, Suresh; Eltze, Christin; Cross, J. H. (Frontiers in Neurology, 2021)
Ketogenic diet therapies (KDT) are high-fat, low carbohydrate diets used as an effective treatment option for drug-resistant epilepsy. There is limited research on the efficacy of KDT for super-refractory status epilepticus (SRSE). We systematically review evidence for use of KDT in children with SRSE and present a single UK tertiary centre's experience. Thirty one articles were included, of which 24 were “medium” or “low” quality. One hundred and forty seven children with SRSE started KDT, of which 141 (96%) achieved ketosis. KDT was started mean 5.3 days (range 1–420) after status epilepticus (SE) started. SRSE resolved in 85/141 (60%) children after mean 6.3 days (range 0–19) post SE onset, but it is unclear whether further treatments were initiated post-KDT. 13/141 (9%) children died. Response to KDT was more likely when initiated earlier (p = 0.03) and in females (p = 0.01). Adverse side effects were reported in 48/141 (34%), mostly gastrointestinal; potentially serious adverse effects occurred in ≤4%. Eight children with SRSE, all diagnosed with febrile infection-related epilepsy syndrome, were treated with KDT at Great Ormond Street Hospital for Children. KDT was initiated enterally at mean day 13.6+/− 5.1 of admission. Seven of 8 (88%) children reported adverse side effects, which were potentially serious in 4/8 (50%), including metabolic acidosis, hypoglycaemia and raised amylase. SE ceased in 6/8 (75%) children after mean 25+/− 9.4 days post onset, but other treatments were often started concomitantly and all children started other treatments post-KDT. Two of 8 (25%) children died during admission and another died post-admission. Four of the remaining 5 children continue to have drug-resistant seizures, one of whom remains on KDT; seizure burden was unknown for one child. Our findings indicate that KDT is possible and safe in children with SRSE. Cessation of SRSE may occur in almost two-thirds of children initiated with KDT, but a causal effect is difficult to determine due to concomitant treatments, treatments started post-KDT and the variable length of time post-KDT onset when SRSE cessation occurs. Given that serious adverse side effects seem rare and response rates are (cautiously) favorable, KDT should be considered as an early treatment option in this group.